2015
DOI: 10.1016/j.humov.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Influences of gender and socioeconomic status on the motor proficiency of children in the UK

Abstract: As the development of movement skills are so crucial to a child's involvement in lifelong physical activity and sport, the purpose of this study was to assess the motor proficiency of children aged 4-7 years (range= 4.3-7.2 years), while considering gender and socioeconomic status. 369 children (176 females, 193 males, aged = 5.96±0.57 years) were assessed for Fine Motor Precision, Fine Motor Integration, Manual Dexterity, Bilateral Co-ordination, Balance, Speed and Agility, Upper-Limb Co-ordination and Streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
132
8
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(166 citation statements)
references
References 29 publications
18
132
8
8
Order By: Relevance
“…‘cutting and pasting’ and ‘(un)dressing independently’. Although contradicted by studies not finding any differences, some studies have suggested that fine motor skills develop earlier in girls than in boys, which might explain the DIF for gender found in this study. Upon inspection, DIF for gender did not seem to be confounded by differences in level of VI, presence of comorbidity or differences related to age.…”
Section: Discussioncontrasting
confidence: 99%
“…‘cutting and pasting’ and ‘(un)dressing independently’. Although contradicted by studies not finding any differences, some studies have suggested that fine motor skills develop earlier in girls than in boys, which might explain the DIF for gender found in this study. Upon inspection, DIF for gender did not seem to be confounded by differences in level of VI, presence of comorbidity or differences related to age.…”
Section: Discussioncontrasting
confidence: 99%
“…10,16,18 However, findings of the current study are consistent with recent reports that have shown similar differences by sex in motor and writing skills in healthy children. 35,36 It is interesting to note that no factors examined in the present study predicted problems with executive functioning, attention, or behavior, deficits that are frequently seen in older children with CHD. 2 In the present study, executive functioning, attention, and behavior were assessed exclusively via parent questionnaires, which may have influenced the results.…”
Section: Discussionmentioning
confidence: 58%
“…Despite this, there are few studies (e.g. Foulkes et al, 2016;Morley et al, 2015) which empirically substantiate claims that British children's FMS proficiency is 'low'.…”
Section: Suggestions Relating To Low Fms Competency Among British Chimentioning
confidence: 99%
“…In the context of England, the most recent changes to the PE curriculum explicitly identified the development of FMS as a key outcome within Key Stage 1 (ages 5-7 years), and the development of fundamental sports skills as key within Key Stage 2 (7-11 years) (Department for Education, 2013). In the English National Curriculum for PE (Department for Education, 2013), the development of particular FMS is emphasised with the Key Stage 1 attainment targets, stating that pupils should: 'master basic movements including running, jumping, throwing and catching,' and the Key Stage 2 attainment targets stating that pupils should: 'use running, jumping, throwing and catching in isolation and in combination'. Despite this focus on FMS, multiple research studies identify concerns that FMS competency among children is low, and that children are not mastering these FMS to their expected age-related developmental capability (Bryant et al, 2016;Foulkes et al, 2015;Morley et al, 2015;O'Brien et al, 2016;Okely and Booth, 2004).…”
Section: Introductionmentioning
confidence: 99%